2019 14th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2019
DOI: 10.1109/hri.2019.8673084
|View full text |Cite
|
Sign up to set email alerts
|

Robot Capability and Intention in Trust-Based Decisions Across Tasks

Abstract: In this paper, we present results from a humansubject study designed to explore two facets of human mental models of robots-inferred capability and intention-and their relationship to overall trust and eventual decisions. In particular, we examine delegation situations characterized by uncertainty, and explore how inferred capability and intention are applied across different tasks. We develop an online survey where human participants decide whether to delegate control to a simulated UAV agent. Our study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…Arguably, trust is most crucial in new and uncertain situations whereby both robot capability and intention can influence outcomes. In very recent work (Xie et al, 2019), we have begun to examine how human mental models of these factors influence decisions to trust robots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arguably, trust is most crucial in new and uncertain situations whereby both robot capability and intention can influence outcomes. In very recent work (Xie et al, 2019), we have begun to examine how human mental models of these factors influence decisions to trust robots.…”
Section: Discussionmentioning
confidence: 99%
“…We believe our results to remain valid when the robot’s actions affect the human participant’s goals. Our recent work (Chen et al, 2018; Xie et al, 2019) includes behavioral measures, such as operator take-overs and greater forms of risk (e.g., in the form of performance bonuses/penalties); these experiments also provide evidence for trust transfer across tasks.…”
Section: Human-subjects Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, robots that came across as transparent, either by providing explanations for its actions [48,49] or simply by providing more information about its actions [50,51], were judged as more trustworthy. At a more cognitive level, one study suggests that robots that took risky actions in an uncertain environment were viewed with distrust [52], although this depends on the individual user's risk appetite [53]. In other work, robots that expressed vulnerability [54] or emotion [55] through natural language were trusted more.…”
Section: Exploiting the Processmentioning
confidence: 99%
“…Some recent works have begun to explore this area. For example, [53] examined two different aspects of trust-trust in a robot's intention and trust in a robot's capability-and demonstrated that these two factors interact to give rise to reliance on the robot. Similarly, [63] demonstrated that trust can be modeled as a latent function (i.e., an infinite-dimensional model of trust) to incorporate different contexts and showed that this approach could capture how trust transfers across different task environments.…”
Section: Challenge Iii: Rich Trust Models For Real-world Scenariosmentioning
confidence: 99%